Synchronization of Reactive Power in Solar Based DG and Voltage Regulated Elements Using Stochastic Optimization Technique - Karuppusamy, P. (Journal of Electrical Engineering and Automation, 2020)
As the distribution generation (DG) based on the solar has attained more prominence and are broadly utilized by multitudes of client and the manufacturers of power on distribution system that is radial. The solar based distributed generation for the radial distribution system affects the changeover functions of the tap changers that are less laden as well as the capacitors connected in shunt and further causes loss of power. The paper attempts in developing an innovative process of synchronization using the stochastic optimization technique the particle swarm optimization to bring together the reactive power of the distribute generation of the solar and the elements that are regulated using the voltage. The synchronization is performed by predicting the load. The procedure for the performing the synchronization is framed on the operational cost and the cost of power loss as multiobjective function. The methodology followed in the paper is examined in the MATLAB over 10 kV, sixteen buses. The observed results were compared with the traditional methodologies to determine the efficacy eluding any failures in the conditions of the GRID.
Keywords: Distributed Generation; Solar Energy; Radial Distribution System; Voltage Regulated Elements; Stochastic Optimization Technique